Analysis of the ecosystem services of mangrove to aquaculture and fisheries in Vietnam - Mangrove and aquaculture in the Mekong River Delta, Vietnam - Truong, Dang Thuy (University of Gothenburg, 2021)
In this study, which will cover six provinces in south Vietnam, we expect to find out the optimal level of mangrove coverage for shrimp farming systems, considering the benefits of mangrove on fishery. Besides, investigation of the determinants of the behavior of converting mangrove to other uses will provide useful information for policy makers towards a better management and conservation of mangrove forests. The project has the following research objectives: (1) Examine the impacts of mangrove on shrimp farming, specifically the impacts of mangrove coverage on shrimp farming productivity and profitability; (2) Examine the impacts of mangrove on the risk of shrimp farming; (3) Estimate the mangrove-fishery linkage; (4) Investigate the determinants of mangrove conversion.

The survey was conducted in communes of six coastal provinces in the south of Vietnam, including Ben Tre, Soc Trang, Tra Vinh, Kien Giang, Ca Mau, and Bac Lieu. From these six provinces, eight locations were selected. Face to face survey was chosen, and each respondent was interviewed using a questionnaire of three parts, including general information of respondent, perception about mangrove of respondent, and aquaculture activities. We surveyed 659 mixed mangrove-shrimp farms. Mangrove forest indicators of analyses at both levels are measured in two ways. One is self-reported by farm managers in household data, and the other is calculated using satellite images. For calculating mangrove coverage of farms (mixed mangrove-shrimp farming system), coordinates of farms are collected during the survey. These coordinates are then used to create boundaries of farms on Google Earth.

In this study, which will cover six provinces in south Vietnam, we expect to find out the optimal level of mangrove coverage for shrimp farming systems, considering the benefits of mangrove on fishery. Besides, investigation of the determinants of the behavior of converting mangrove to other uses will provide useful information for policy makers towards a better management and conservation of mangrove forests. The project has the following research objectives: (1) Examine the impacts of mangrove on shrimp farming, specifically the impacts of mangrove coverage on shrimp farming productivity and profitability; (2) Examine the impacts of mangrove on the risk of shrimp farming; (3) Estimate the mangrove-fishery linkage; (4) Investigate the determinants of mangrove conversion.

The survey was conducted in communes of six coastal provinces in the south of Vietnam, including Ben Tre, Soc Trang, Tra Vinh, Kien Giang, Ca Mau, and Bac Lieu. From these six provinces, eight locations were selected. Face to face survey was chosen, and each respondent was interviewed using a questionnaire of three parts, including general information of respondent, perception about mangrove of respondent, and aquaculture activities. We surveyed 659 mixed mangrove-shrimp farms. Mangrove forest indicators of analyses at both levels are measured in two ways. One is self-reported by farm managers in household data, and the other is calculated using satellite images. For calculating mangrove coverage of farms (mixed mangrove-shrimp farming system), coordinates of farms are collected during the survey. These coordinates are then used to create boundaries of farms on Google Earth.
Analysis of the ecosystem services of mangrove to aquaculture and fisheries in Vietnam - Mangrove and aquaculture in the Mekong River Delta, Vietnam
Keywords: Aquaculture; Akvakultur; mangrove forest; profitability; lönsamhet; Environmental Sciences; Miljövetenskap; Economics and Business; Ekonomi och näringsliv; Farming; Areella näringar; Economy; Ekonomi; Environment; Miljö